Huangbaiye Tuji combined with Longdan Xiegan Decoction for anal cryptitis: Analysis of clinical efficacy and its influence on disease recurrence: Huangbaiye Tuji combined with LDXGD for the treatment of AC - Yang, Lin; Liu, Jiazhen; Liang, Jingyang; Wang, Yan; Liu, Lu (Cellular and Molecular Biology, 2024)
Given the rising incidence of anal cryptitis (AC) in recent years, it is of great significance to find an effective and safe treatment scheme to ensure the healthy life of patients. In this study, we explored the clinical efficacy of Huangbaiye Tuji combined with Longdan Xiegan Decoction (LDXGD) for AC and observed changes in patients' cellular immune function, which can provide a new reference for future treatment of AC. By comparison, we found that compared with Huangbaiye Tuji treatment alone, its combination with LDXGD had better clinical efficacy and high safety, contributing to more significant relief of inflammatory reaction and oxidative stress. In terms of immune function, the patients' humoral and cellular immunity were more effectively enhanced after the combination therapy. According to these results, it is recommended to use Huangbaiye Tuji combined with LDXGD in the treatment of AC.